ORGANIZING AND DEVELOPING PUBLIC PROCUREMENT IN THE REPUBLIC OF UZBEKISTAN (Modern education and development, 2025)
This article explores ways to enhance the efficiency of public procurement in Uzbekistan and its role in improving the effectiveness of public budget expenditures and financial management.